Effects of aminooxyacetic acid on learning and memory function and neurochemical changes in chronic alcoholism - Hongbo Jiang; Xunling Wang; Yingwei Liang; Yinghan Hou; Xinping Yue; Zhiyi Zhang; Dan Chen; Xinyi Fan; Ailin Du (Brain Research Bulletin)
Objective: This study aimed to investigate the effect of aminooxyacetic acid (AOAA) on cognitive function, particularly learning and memory, in a rat model of chronic alcoholism. Additionally, the study explored changes in cystathionine β-synthase (CBS), hydrogen sulfide (H₂S), and serotonin (5-HT) levels in the prefrontal cortex to understand the potential neurochemical mechanisms involved. Methods: Sixty-four male SD rats were randomly divided into four groups, with 16 rats in each: Con, Con + AOAA, Model, and Model + AOAA. The Model group received a 6 % ethanol solution for 28 days. From day 14, the Model + AOAA group was treated with daily intraperitoneal injections of AOAA (5 mg/kg) for 14 consecutive days. Cognitive function was assessed using the Morris water maze, mitochondrial function was evaluated through ATPase activity, and H₂S levels were measured. CBS and 5-HT levels in the prefrontal cortex were analyzed by immunohistochemistry. Results: Compared to the control groups, rats in the Model group exhibited significant impairments in learning and memory, increased CBS expression, elevated H₂S levels, and decreased 5-HT release. AOAA treatment improved memory performance, reduced CBS expression and H₂S levels, and increased 5-HT release, although these measures did not fully return to baseline. No significant differences were observed between the two control groups. Conclusion: AOAA may alleviate cognitive deficits associated with chronic alcoholism by inhibiting CBS expression, reducing H₂S levels, and enhancing 5-HT release in the prefrontal cortex. These findings suggest AOAA as a potential therapeutic strategy for alcohol-induced cognitive impairments.